2010
DOI: 10.1021/jm901872v
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Fluoroketone Inhibitors of Group VIA Calcium-Independent Phospholipase A2

Abstract: Group VIA calcium-independent phospholipase A2 (GVIA iPLA2) has recently emerged as a novel pharmaceutical target. We have now explored the structure-activity relationship between fluoroketones and GVIA iPLA2 inhibition. The presence of a naphthyl group proved to be of paramount importance. 1,1,1-Trifluoro-6-(naphthalen-2-yl)hexan-2-one (FKGK18) is the most potent inhibitor of GVIA iPLA2 (XI(50) 0.0002) ever reported. Being 195 and >455 times more potent for GVIA iPLA2 than for GIVA cPLA2 and GV sPLA2, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
108
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 47 publications
0
108
0
3
Order By: Relevance
“…We have also shown that, at the concentration used in this study (1 mM), the inhibitor blocks essentially all measurable Ca 2+ -dependent PLA 2 activity of cell homogenates, leaving the Ca 2+ -independent activity unchanged (47,67,69). FKGK18, a member of a family of polyfluoroketone-containing compounds, is the most potent iPLA 2 b inhibitor reported, completely blocking iPLA 2 b activity at concentrations $200 times lower than those required for inhibition of other PLA 2 activities, which makes it a valuable tool to explore the role of iPLA 2 b in cells and in in vivo models (11,41). In keeping with this observation, very recent data in pancreatic b cells show that FKGK18 blocks iPLA 2 b-mediated responses in these cells while leaving the cPLA 2 a-dependent ones unchanged (70).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have also shown that, at the concentration used in this study (1 mM), the inhibitor blocks essentially all measurable Ca 2+ -dependent PLA 2 activity of cell homogenates, leaving the Ca 2+ -independent activity unchanged (47,67,69). FKGK18, a member of a family of polyfluoroketone-containing compounds, is the most potent iPLA 2 b inhibitor reported, completely blocking iPLA 2 b activity at concentrations $200 times lower than those required for inhibition of other PLA 2 activities, which makes it a valuable tool to explore the role of iPLA 2 b in cells and in in vivo models (11,41). In keeping with this observation, very recent data in pancreatic b cells show that FKGK18 blocks iPLA 2 b-mediated responses in these cells while leaving the cPLA 2 a-dependent ones unchanged (70).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel studies, we also determined the effect of inhibiting iPLA 2 b with the novel selective inhibitor FKGK18 (41). In stark contrast with the experiments using pyrrophenone, the zymosanstimulated decreases in PC and PI molecular species were the same whether or not FKGK18 was present in the incubations (Fig.…”
Section: Aa-containing Species In Macrophagesmentioning
confidence: 97%
See 1 more Smart Citation
“…Because FK inhibitors target serine active sites, they could potentially also inhibit cPLA 2 s. However, modifi cation of the FK group along with addition of a hydrophobic terminus, connected by a medium-length carbon chain to mimic the fatty acid chain, conferred selectivity of the FK compounds for iPLA 2 versus sPLA 2 or cPLA 2 ( 157 ), and earlier generation FK compounds (FKGK11 and FKGK2) were found to be benefi cial in an experimental autoimmune encephalomyelitis animal model of multiple sclerosis ( 158 ). Subsequently, the FK-based inhibitor of iPLA 2 ␤ (FKGK18) was found to be 7-fold more potent than FKGK11 toward iPLA 2 ␤ ; 195 and >455 times more potent for iPLA 2 ␤ than for group IVA cPLA 2 and group V sPLA 2 , respectively ( 159 ); and effective in cell-based studies ( 160 ) and in countering T1D ( 161 ).…”
Section: Modulation Of Ipla 2 ␤mentioning
confidence: 99%
“…We thus expanded our initial inhibitor discovery work first to mammalian sPLA 2 s (112), including the use of antisense technology (113), and then to other PLA 2 groups-especially the intracellular cPLA 2 and iPLA 2 -by activated ketones (114,115), fluorophosphonates (116), and other traditional inhibitors (98). In the last decade, this has expanded into a long collaboration with Professor George Kokotos from the University of Athens (9), in which we are designing and testing novel inhibitors including oxoamides (117-120), polyfluoroketones (121,122), and thiazolyl ketones (123). Specifically, we've leaned on insights from molecular dynamics and simulations to inform rational drug design and medicinal chemistry efforts capped off with extensive biochemical characterization.…”
Section: A Turning Point For Lipid Signalingmentioning
confidence: 99%